How to be or not to be? A critical dialogue on the limitations and opportunities of academic development in the current higher education context - Behari-Leak, K.; Vorster, J.E.; Chitanand, N.; Ganas, R.; Padayachee, K.; Merckel, V.; Masehela, L. (South African Journal of Higher Education, 2018)
In the tumultuous time we find ourselves, debates about pedagogy have taken centre stage once again. Concerns raised by the student protests of 2015 and 2016 have highlighted the urgent need to re-think traditional teaching, learning and assessment practices, as well as the development of decolonised and transformative curricula. Traditional notions of academic and professional development are now being tested and contested, insofar as they are able to respond to student challenges in appropriate, responsive, legitimate and relevant ways. As a professional organisation dedicated to supporting learning and teaching, the executive team of HELTASA responded to the challenge in this paper by engaging with perspectives on the purpose, role and conceptualisation of AD in the current decolonial moment in the South African Higher Education landscape. Critical processes that enable academics to engage, share thoughts and debate epistemological, pedagogical and methodological options to support students and academics are much needed. And the context and spirit in which these debates occur may be as important as the debates themselves. At its annual conference, the executive team facilitated a critical dialogue with conference delegates on the limitations and opportunities of AD in our current context. Given the diverse teaching and learning contexts and institutional differentiation in the sector, this paper explores individual and collective theorised observations, reflections and experiences of the seven facilitators who led the CD. These reflections were analysed and discussed against the backdrop of AD as well as the affordances of CD as a participatory learning and engagement methodology. The findings showed that there is dire need to re-imagine, not only AD’s role but alternative forms of critical engagement in the sector.